2016
DOI: 10.18043/ncm.77.6.394
|View full text |Cite
|
Sign up to set email alerts
|

CenteringPregnancy: Meeting the Quadruple Aim in Prenatal Care

Abstract: CenteringPregnancy is a group prenatal care model that engages pregnant women in their care, which results in promising health and system outcomes. This commentary will review this innovative care model with a focus on patient experience, population health outcomes, cost effectiveness, and provider experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…5,6 In many studies CP is associated with positive maternal and neonatal outcomes, including a decrease in low birth weight (LBW), preterm birth (PTB) rates, 7,8 infants small for gestational age (SGA), neonatal intensive care (NICU) admission rates, better Apgar scores, and higher breastfeeding rates. [9][10][11][12][13][14] However, given the robustness of most studies the effects of CP in systematic reviews remains inconclusive. Several systematic reviews found no significant decrease in adverse perinatal outcomes [15][16][17] among women participating in CP or group antenatal care.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In many studies CP is associated with positive maternal and neonatal outcomes, including a decrease in low birth weight (LBW), preterm birth (PTB) rates, 7,8 infants small for gestational age (SGA), neonatal intensive care (NICU) admission rates, better Apgar scores, and higher breastfeeding rates. [9][10][11][12][13][14] However, given the robustness of most studies the effects of CP in systematic reviews remains inconclusive. Several systematic reviews found no significant decrease in adverse perinatal outcomes [15][16][17] among women participating in CP or group antenatal care.…”
Section: Introductionmentioning
confidence: 99%
“…Antenatal care in the Netherlands traditionally consists of individual visits ( Koster et al, 2015 ). With the implementation of CP, these visits have been replaced by group sessions ( Rising, 1998 , Rising et al, 2004 ), thereby providing healthcare workers more time with pregnant women and for them to engage in mutual learning and health education ( Strickland et al, 2016 ). Internationally, CP is associated with positive maternal and neonatal outcomes ( Ickovics et al, 2003 , Ickovics et al, 2007 , Jafari et al, 2010 , Picklesimer et al, 2012 , Sheeder et al, 2012 , Tanner-Smith et al, 2013 , Strickland et al, 2016 , Cunningham et al, 2017 , Ghani, 2018 , Abshire et al, 2019 , Adaji et al, 2019 , Crockett et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the implementation of CP, these visits have been replaced by group sessions ( Rising, 1998 , Rising et al, 2004 ), thereby providing healthcare workers more time with pregnant women and for them to engage in mutual learning and health education ( Strickland et al, 2016 ). Internationally, CP is associated with positive maternal and neonatal outcomes ( Ickovics et al, 2003 , Ickovics et al, 2007 , Jafari et al, 2010 , Picklesimer et al, 2012 , Sheeder et al, 2012 , Tanner-Smith et al, 2013 , Strickland et al, 2016 , Cunningham et al, 2017 , Ghani, 2018 , Abshire et al, 2019 , Adaji et al, 2019 , Crockett et al, 2019 ). Moreover, CP has been related to greater satisfaction with antenatal care ( Ickovics et al, 2007 , Craswell et al, 2016 ), and a greater number of antenatal care visits ( Eluwa et al, 2018 , Abshire et al, 2019 , Heberlein et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The plan's priorities include pregnancy intendedness, obesity and related conditions, and substance abuse. The plan's addendum discusses the role of access to care, mental health, and life planning in addressing preconception health and women's wellness in our state.Another article in this issue of the NCMJ, by Carmen Strickland and colleagues [8], documents the benefits of group prenatal care. This model can strengthen patient and provider engagement, and evidence has emerged on improvements in preterm birth, family planning utilization, and birth outcomes, as well as cost savings.…”
mentioning
confidence: 99%
“…Another article in this issue of the NCMJ, by Carmen Strickland and colleagues [8], documents the benefits of group prenatal care. This model can strengthen patient and provider engagement, and evidence has emerged on improvements in preterm birth, family planning utilization, and birth outcomes, as well as cost savings.…”
mentioning
confidence: 99%